2003
DOI: 10.1182/blood-2002-08-2408
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal T-cell expansions in asymptomatic individuals and in patients with large granular leukemia consist of cytotoxic effector T cells expressing the activating CD94:NKG2C/E and NKD2D killer cell receptors

Abstract: We have analyzed the phenotype, cytokine profile, and mitotic history (telomere length) of monoclonal T-cell expansions in 5 CD3 ؉ T-cell large granular lymphocyte (TLGL) leukemia patients by fluorescence activated cell sorting (FACS) and single-cell polymerase chain reaction (PCR). We confirm that the common phenotype of TLGL leukemia is CD3 ؉ CD8 ؉ CD45RA ؉ CD27 ؊ CD94 ؉ (CD57 ؉ ). Interestingly, the C-type lectin-like type killer cell receptor CD94 was invariably associated with the activating form of its s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 46 publications
(63 reference statements)
2
61
1
1
Order By: Relevance
“…As a consequence, a small amount of activated cells should be detected among the clonal population they found, as the expression of the persisting stimulation. 28 Our results seems to validate this hypothesis, by demonstrating the expression of the raft marker GM1 bright , identifying activated cells, expressed in a small but well-defined percentage of GL in all patients with LDGL studied. In addition, since the percentage of GM1 bright GL and the lymphocytosis are extremely stable during time in all the patients analyzed (see Figure 3), our results point to a role of these activated cells in the biology of GL proliferation, possibly involved in the renewal of circulating GL.…”
Section: Figuresupporting
confidence: 71%
See 2 more Smart Citations
“…As a consequence, a small amount of activated cells should be detected among the clonal population they found, as the expression of the persisting stimulation. 28 Our results seems to validate this hypothesis, by demonstrating the expression of the raft marker GM1 bright , identifying activated cells, expressed in a small but well-defined percentage of GL in all patients with LDGL studied. In addition, since the percentage of GM1 bright GL and the lymphocytosis are extremely stable during time in all the patients analyzed (see Figure 3), our results point to a role of these activated cells in the biology of GL proliferation, possibly involved in the renewal of circulating GL.…”
Section: Figuresupporting
confidence: 71%
“…It is not clear whether the lack of CD28, together with the presence of activating NK receptors (namely CD94/NKG2C and NKG2D), which are commonly demonstrated in GL of CD3 þ LDGL patients, could indeed be related to the peculiar pattern of rafts' expression. 28 It is interesting to note that CD94 has been reported to bind HLA-E antigens 29,30 and that this interaction is particularly efficient in the recognition of some viral antigens, namely CMV, EBV and influenza viruses. 31 It can be speculated that the multiple activating signals released by different activating receptors (CD94/NKG2C, NKG2D) 28,32 might be involved in the expression of GM1 bright on the GL surface, although it should be noted that the percentage of cases characterized by the expression of CD94 includes only a fraction of patients under study and NKG2D was not expressed in two cases.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…FACS re-analysis (>98% cells positive for GL183) and limited dilution cloning (10/ 10 growing clones were positive for GL183) confirmed the purity of the sorted cells. cDNA was prepared from 3,000-5,000 sorted cells and spectratyping was performed as described [43].…”
Section: Hla-c Typing and Tcr Usage Determinationmentioning
confidence: 99%
“…Antigen stimulation of LGL effector cells and triggering of effector molecules may dysregulate immune mechanisms and thereby cause clinical problems (Bigouret et al, 2003). In line with the idea of antigen-activated cytotoxic effector cells, we have previously shown that T-LGL proliferations often display a polyclonal to oligoclonal Vb repertoire, with many cases showing one or more dominant clones with restricted Vb usage or even clear monoclonal Vb usage (Langerak et al, 2001).…”
mentioning
confidence: 91%